2022
DOI: 10.1039/d2qi01427k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing photoluminescence efficiency of atomically precise copper(i) nanoclusters through a solvent-induced structural transformation

Abstract: Atomically precise copper(I) nanoclusters (CuNCs) with high photoluminescence (PL) efficiency and relatively short lifetime could be promising non-precious metal-based phosphorescent emitters for organic light-emitting diodes (OLEDs), but the synthesis of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…Each Cu 12 cluster core is stabilized by 8 PhCOO − , 4 PhC−C −, and 4 electroneutral 4,4’‐bipyridine ligands, indicating that Cu in Cu 12 ‐1 exists as Cu(I), and Cu 12 ‐1 contains no free valence electron (12‐8‐4=0). X‐ray photoelectron spectroscopy (XPS) clearly reveals that the binding energy for Cu 2p 3/2 of Cu 12 ‐1 is located at 932.97 eV, similar to other Cu(I) complexes, [44] further confirming that Cu are +1 valence in Cu 12 ‐1 (Figure S4). PhC=C − ligands adopt two types of coordination modes with Cu atoms (μ 3 : η 1 : η 1 : η 2 and μ 4 : η 1 : η 1 : η 2 : η 2 ) (Figure 1c) and the Cu−C bond lengths range from 1.906 Å to 2.071 Å.…”
Section: Resultsmentioning
confidence: 54%
“…Each Cu 12 cluster core is stabilized by 8 PhCOO − , 4 PhC−C −, and 4 electroneutral 4,4’‐bipyridine ligands, indicating that Cu in Cu 12 ‐1 exists as Cu(I), and Cu 12 ‐1 contains no free valence electron (12‐8‐4=0). X‐ray photoelectron spectroscopy (XPS) clearly reveals that the binding energy for Cu 2p 3/2 of Cu 12 ‐1 is located at 932.97 eV, similar to other Cu(I) complexes, [44] further confirming that Cu are +1 valence in Cu 12 ‐1 (Figure S4). PhC=C − ligands adopt two types of coordination modes with Cu atoms (μ 3 : η 1 : η 1 : η 2 and μ 4 : η 1 : η 1 : η 2 : η 2 ) (Figure 1c) and the Cu−C bond lengths range from 1.906 Å to 2.071 Å.…”
Section: Resultsmentioning
confidence: 54%
“…The usage of other Cu‐NCs (e.g., Cu10 and Cu18 ) that are not stable in basic conditions [16b] much lower the yield to 24 % and 32 %, respectively, revealing the chemical stability of Cu‐NCs played an important role during the catalysis. Furthermore, the reaction kinetics also were studied and the results revealed that the reaction followed the pseudo‐first‐order rate dependence on phenylacetylene concentration, as indicated by the linear fitting of the ln( C 0 / C ) vs reaction time (t) curve (Figure S20).…”
Section: Resultsmentioning
confidence: 99%
“…These in turn control the spatial distribution of the ligand shell and consequently influence their optical signatures. Recently, considerable attempts have been deployed to design highly luminescent MNCs with tuneable optical properties by varying various external parameters post their synthesis [20–22] . Among these, solvent‐induced tailoring of the optical properties of MNCs is gaining exceptionally pronounced interest over the last decade [23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable attempts have been deployed to design highly luminescent MNCs with tuneable optical properties by varying various external parameters post their synthesis. [20][21][22] Among these, solvent-induced tailoring of the optical properties of MNCs is gaining exceptionally pronounced interest over the last decade. [23,24] The variation in the solvent can also evolve the possibility of inter-cluster conversion which in turn modulates their optical properties.…”
Section: Introductionmentioning
confidence: 99%